Ultrasonic propagation in cancellous bone - McKelvie, Marion Lindsay (1988)
The thesis covers two main areas of work. The first is detailed experimental work and the second is the evaluation of existing ultrasonic theories in attempt to apply them to the propagation in cancellous bone. The work is related to a new technique which uses ultrasonic attenuation to measure and predict osteoporosis, especially in the elderly population. The ultrasonic attenuation, the longitudinal ultrasonic velocity, the scattering effect and the attenuation as a function of frequency were measured on a range of cancellous bone samples, from healthy to severely osteoporotic, and also a few cortical samples. The cancellous bone was human os calces and vertebrae. The relationships between the ultrasonic propagation and the structural parameters and density of the bone were investigated, and were considered both for whole bones and separate purely cancellous samples. Image analysis of photomicrographs taken under low magnification was carried out to find the architectural parameters of the bone structure. The ultrasonic measurements were also compared with quantitative computed tomography assessment and compressive strength testing. Many theories which are currently used to evaluate ultrasonic propagation in a porous material are reviewed, and three particular ones are developed in detail and applied to models of cancellous bone. The self consistent theory (SCT), Biot's theory and the multiple scattering theory based on the work of Waterman and Truell were all assessed for their limits with repect to this particular application, and each had its own deficiencies. The Blot theory, however, proved the most successful at predicting the experimental attenuation results observed, but still only in a limited way.
HydraID: hull:8397 Hydra Discover Access Group: public EThOS identifer: uk.bl.ethos.236233
Keywords: Physics